Counseling Entrepreneurship Based on Technology for Beginners at SMAN 7 Kepulauan Selayar - Sukarman; Agustini (Journal GoodWill, 2025)
This study aims to explore the implementation and effectiveness of technology-based entrepreneurship counseling for beginner-level students at SMAN 7 Kepulauan Selayar. The counseling program was designed using an interactive and participatory approach to improve students' understanding, interest, and readiness in initiating digital-based business ventures. The research employed a descriptive qualitative method involving 50 students, with data collected through observation, open interviews, documentation, and pre-post tests. The counseling activities included modules on formulating business ideas, simple business planning, digital marketing strategies, technology risk management, and ethical aspects of digital entrepreneurship. Findings indicate that 85% of participants improved their conceptual understanding, and 70% successfully developed simple business plans, while most showed significant enthusiasm in digital marketing practices. SWOT analysis revealed that while the content was accessible and well-received, challenges such as unequal access to digital devices persisted. Evaluation results further showed that 92% of participants were satisfied with the program, and 80% expressed interest in continuing to more advanced stages. This study underscores the importance of integrating technology in entrepreneurship education to build digital business competencies among youth. It recommends extending the training duration, involving local business practitioners, and forming school-based digital entrepreneur communities. Overall, the program proved effective in enhancing entrepreneurial knowledge, skills, and confidence, while fostering innovation and contributing to the local entrepreneurial ecosystem. The findings highlight the need for continuous support and structured follow-up to ensure sustainable impact.